Pemberdayaan Keluarga Sebagai Pencegahan Demensia pada Lansia - Sa’diyah, Halimatus; Indarwati, Retno; Sari, Dianis Wulan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to see how the relationship between family empowerment and efforts to prevent dementia behavior in the elderly. The method used was a systematic review of three databases; Scopus, PubMed, and Web of Science using various combinations of keywords related to